When Inflation Persistence Really Matters: Two examples - Tatiana Kirsanova; David Vines; Simon Wren-Lewis (Kiel Institute for the World Economy (IfW), 2007)
In this paper we present two examples where the presence of inflation persistence could influence the qualitative nature of monetary policy. In the first case the desirability of a monetary policy regime comes under question when extensive inflation persistence exists. In the second case the direction in which interest rates move following a cost push shock changes when inflation persistence becomes important. In both cases, inflation persistence is central to the process influencing policy.
Keywords: E63; E61; E52; 330; Inflation Persistence; Macroeconomic Stabilisation